Design and fabrication of gout patient movable device / Wan Ahmad Syamil Asyraf Wan Azman - Wan Azman, Wan Ahmad Syamil Asyraf (2022)
Gout is the most common form of inflammatory arthritis that can be treated. There has yet to be a prevalence study on gout in Malaysians. For a few days or two to three weeks, the pain feels "like a thousand needles under your skin," as most gout patients will tell you. During an attack, the majority of them could barely walk. The problem is most of movable device that gout patient use now is not effective enough to help them walk. For example, a cane. Even though some manufacturers make it big and strong to support weight of a big body person, but they still need to use a lot of energy to move their body and walk. Some of the cane looked not so ergonomic and cannot use for a long time.